2006
DOI: 10.1098/rspb.2006.3467
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic predation events and population persistence in bighorn sheep

Abstract: Many studies have reported temporal changes in the relative importance of density-dependence and environmental stochasticity in affecting population growth rates, but they typically assume that the predominant factor limiting growth remains constant over long periods of time. Stochastic switches in limiting factors that persist for multiple time-steps have received little attention, but most wild populations may periodically experience such switches. Here, we consider the dynamics of three populations of indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
170
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 34 publications
8
170
1
2
Order By: Relevance
“…1A and 2A and Table S1). Initial mixed models accounted for density-dependent effects, using population size as a fixed effect, but we found these to be misleading; the Ram Mountain population has increased dramatically and then declined over the past 40 y, and the low-density decline phase has shown possible time-lag effects and major effects of sudden changes in cougar (Puma concolor) predation (37). Because our models detected and predicted unrealistic positive density dependence, we assumed density independence over the entire time series.…”
Section: Methodsmentioning
confidence: 89%
“…1A and 2A and Table S1). Initial mixed models accounted for density-dependent effects, using population size as a fixed effect, but we found these to be misleading; the Ram Mountain population has increased dramatically and then declined over the past 40 y, and the low-density decline phase has shown possible time-lag effects and major effects of sudden changes in cougar (Puma concolor) predation (37). Because our models detected and predicted unrealistic positive density dependence, we assumed density independence over the entire time series.…”
Section: Methodsmentioning
confidence: 89%
“…Between 1988 and 2010, census size fluctuated between 38 and 210 sheep, declining recently because of low recruitment (Jorgenson et al, 1997) and cougar (Puma concolor) predation (Festa-Bianchet et al, 2006).…”
Section: Study Populationsmentioning
confidence: 99%
“…To explain the decline, by way of hypothesis, the various proximate factors that can negatively affect sheep dynamics, apart from disease, are (1) population density, (2) fecundity, (3) competition for forage from other grazers, (4) predation, and (5) poor habitat (Cowan 1947;Stelfox 1971;Geist 1971;Jorgenson et al 1997;Festa-Bianchet et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…At two localities, telemetry studies revealed that individual Cougars were having a major impact on small, isolated populations of sheep (Festa-Bianchet et al 2006). The declines were halted after the death of these individual Cougars.…”
Section: Predationmentioning
confidence: 99%